Variations in the origins and absence of the common digital arteries of the hand: a cadaveric study. (December 2018) - Hashem, Ahmed M.; Knackstedt, Rebecca W.; Bernard, Steven; Hendrickson, Mark; McBride, Jennifer M.; Djohan, Risal
We studied anomalies of the common digital arteries by dissecting 33 fresh cadaver hands under magnification. In the majority of the dissected hands (25 hands), common digital arteries took off from the superficial palmar arch and ran superficial and parallel to the flexor tendons. Variations were found in eight out of 33 hands. In four hands the common digital artery to the second web space was replaced by an atypical vessel, originating from the deep palmar arch, that crossed posterior to the index flexor tendons proximal to the A1 pulley. In eight hands, the common digital artery to the fourth web space was replaced by an atypical deeper vessel, originating from the superficial palmar arch and crossing posterior to the little finger flexors. No nerve anomalies were identified. Unrecognized, these atypical arteries to the second and/or fourth web spaces could lead to vascular complications during surgery, especially pollicization.